Composite positive active material and preparation method thereof, positive pole piece and secondary battery

By forming a porous metal oxide and conductive polymer cladding on the positive electrode active material matrix, the problem of insufficient overcharge resistance when increasing the energy density of NCM materials is solved, and higher overcharge resistance and electronic conductivity are achieved.

CN119627057APending Publication Date: 2025-03-14NIO BATTERY TECH (ANHUI) CO LTD
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202311176671.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

While increasing the energy density of NCM materials, their overcharge resistance still needs to be improved, resulting in a decrease in the electrochemical stability, mechanical stability and thermal stability of the material.

Method used

A composite positive electrode active material is used, which includes a positive electrode active material matrix, a porous metal oxide cladding layer and a conductive polymer cladding layer. The porous metal oxide coating has good thermal stability and lithium ion transport capability, while the conductive polymer coating makes up for the electrochemical inertia of the metal oxide and improves the electronic conductivity.

Benefits of technology

The overcharge resistance of the positive electrode active material is significantly improved, and its electronic conductivity is improved, solving the problem of the reduction in the conductivity of the simple porous metal oxide coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627057A_ABST
    Figure CN119627057A_ABST
Patent Text Reader

Abstract

The invention relates to a composite positive active material and a preparation method thereof, a positive pole piece and a secondary battery. The composite positive electrode active material comprises a positive electrode active material substrate, a porous metal oxide coating layer arranged on the surface of the positive electrode active material substrate and a conductive polymer coating layer arranged on the surface of the porous metal oxide coating layer. In the composite positive electrode active material, the electrochemical inert porous metal oxide coating layer has good thermal stability and is beneficial to stabilization of a crystal structure and inhibition of surface side reaction, and in addition, the porous structure is beneficial to transmission of lithium ions and storage of oxygen free radicals separated out due to structural collapse of a positive electrode active material matrix in the overcharge process; severe reaction with electrolyte is relieved, and overcharge failure of the positive electrode active material is slowed down. The conductive polymer coating layer can make up the electrochemical inertness of the metal oxide and improve the electronic conductivity of the positive electrode active material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of batteries, and in particular to a composite positive electrode active material and a preparation method thereof, a positive electrode sheet and a secondary battery. Background Art

[0002] At present, electric vehicles are developing more and more rapidly. However, although electric vehicles have improved their advantages in driving quality, vehicle cost, and vehicle purchase subsidies compared to fuel vehicles, the public's acceptance of electric vehicles is still lower than expected, mainly due to the range and safety. In order to improve the range, R&D personnel are actively developing materials with higher energy density. Among them, NCM (nickel-cobalt-manganese ternary material) has gradually become one of the mainstream high-energy density materials due to its high energy density, high platform potential, good rate performance and low cost. However, the improvement of NCM energy density has also brought a series of problems, such as the material's overcharge resistance still needs to be improved. Summary of the invention

[0003] Based on this, it is necessary to provide a composite positive electrode active material and a preparation method thereof that can improve overcharge resistance.

[0004] In addition, it is also necessary to provide a positive electrode sheet and a secondary battery comprising the above composite positive electrode active material.

[0005] A composite positive electrode active material comprises: a positive electrode active material matrix, a porous metal oxide coating layer arranged on the surface of the positive electrode active material matrix, and a conductive polymer coating layer arranged on the surface of the porous metal oxide coating layer.

[0006] In some embodiments, the composite positive electrode active material satisfies at least one of the following conditions:

[0007] (1) The material of the porous metal oxide coating layer is selected from any one or more of aluminum oxide, magnesium oxide, zirconium oxide, zinc oxide, yttrium oxide, nickel oxide, copper oxide and titanium oxide;

[0008] (2) The mass ratio of the porous metal oxide coating layer to the positive electrode active material matrix is ​​1:(200-10000);

[0009] (3) The material of the conductive polymer coating layer is selected from any one or more of polyaniline, doped polyaniline, polypyrrole, doped polypyrrole, polythiophene, doped polythiophene, polyphenylene sulfide and doped polyphenylene sulfide;

[0010] (4) at least a portion of the conductive polymer coating layer is located in the pores on the surface of the porous metal oxide coating layer;

[0011] (5) The mass ratio of the conductive polymer coating layer to the porous metal oxide coating layer is (1-100):1;

[0012] (6) The positive electrode active material matrix includes a transition metal oxide material, and the transition metal oxide material includes nickel element.

[0013] In some embodiments, in the transition metal oxide material, the molar percentage of nickel element to the total molar percentage of transition metal elements is ≥ 60%.

[0014] In some embodiments, in the transition metal oxide material, the molar percentage of nickel element accounts for ≥80% of the total molar percentage of transition metal elements.

[0015] A method for preparing a composite positive electrode active material comprises the following steps:

[0016] (1) forming a porous metal oxide coating layer on the surface of the positive electrode active material matrix;

[0017] (2) forming a conductive polymer coating layer on the surface of the porous metal oxide coating layer to obtain a composite positive electrode active material.

[0018] In some embodiments, the step of forming a porous metal oxide coating layer on the surface of the positive electrode active material matrix includes:

[0019] Mixing the raw material for preparing the positive electrode active material matrix in the form of a metal salt solution with an aqueous solution containing a complexing agent to prepare a metal complex solution;

[0020] drying the metal complex solution to convert the sol into a gel;

[0021] The gel is mixed with a porous metal oxide and calcined at 700° C. to 900° C. for 9 h to 15 h to form the porous metal oxide coating layer on the surface of the positive electrode active material matrix.

[0022] In some of the embodiments, the porous metal oxide is prepared by secondary anodization.

[0023] In some embodiments, the complexing agent is selected from any one or more of inorganic phosphates, alcohol amines, aminocarboxylic acids, hydroxycarboxylates, organic phosphonates and polyacrylic acids.

[0024] In some embodiments, the average pore size of the porous metal oxide coating layer is 10 nm to 900 nm.

[0025] In some embodiments, the porosity of the porous metal oxide coating layer is 50% to 90%.

[0026] In some embodiments, the specific surface area of ​​the porous metal oxide coating layer is 0.5 m 2 / g~1.5m 2 / g.

[0027] In some embodiments, the step of forming a conductive polymer coating layer on the surface of the porous metal oxide coating layer comprises:

[0028] An acidic solution containing monomers for forming the conductive polymer is mixed and stirred with a positive electrode active material matrix coated with a porous metal oxide coating layer. Under the action of an initiator, the monomers for forming the conductive polymer are in situ polymerized using the holes in the porous metal oxide coating layer as a template to form the conductive polymer coating layer on the surface of the porous metal oxide coating layer.

[0029] In some embodiments, the step of forming a conductive polymer coating layer on the surface of the porous metal oxide coating layer satisfies one or more of the following conditions:

[0030] (1) in the step of allowing the monomer for forming the conductive polymer to be in-situ polymerized using the pores in the porous metal oxide coating layer as a template, first stirring at 0° C. to 10° C. for 7 h to 10 h, and then standing for 24 h to 72 h;

[0031] (2) The monomer used to form the conductive polymer is selected from any one or more of aniline, pyrrole, thiophene and phenylene sulfide;

[0032] (3) The acidic solution includes any one of hydrochloric acid and phytic acid.

[0033] A positive electrode plate comprises: a current collector and an active material layer arranged on the current collector, wherein the active material layer comprises the above-mentioned composite positive electrode active material or the composite positive electrode active material prepared by the above-mentioned method for preparing the composite positive electrode active material.

[0034] A secondary battery comprises the above-mentioned positive electrode plate.

[0035] The above-mentioned composite positive electrode active material includes a positive electrode active material matrix and a porous metal oxide coating layer and a conductive polymer coating layer formed on the surface of the positive electrode active material matrix. The electrochemically inert porous metal oxide coating layer has good thermal stability, which helps to stabilize the crystal structure and inhibit surface side reactions. In addition, the porous structure helps the transmission of lithium ions, and is also conducive to the storage of oxygen free radicals precipitated due to structural collapse of the positive electrode active material matrix during overcharging, alleviating the occurrence of violent reactions with the electrolyte, and slowing down the overcharge failure of the positive electrode active material. However, although the simple porous metal oxide coating layer can improve the overcharge resistance, the conductivity is significantly reduced compared with the uncoated positive electrode active material matrix, and it cannot be used in practice. The conductive polymer coating layer can make up for the electrochemical inertness of the metal oxide and improve the electronic conductivity of the positive electrode active material. Experiments have shown that the composite positive electrode active material has improved overcharge resistance and better electronic conductivity than the uncoated positive electrode active material matrix. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 The process flow chart of the preparation method of the composite positive electrode active material in some embodiments of the present invention. DETAILED DESCRIPTION

[0037] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively below in conjunction with the specific embodiments. Preferred embodiments of the present invention are provided in the specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0039] Unless otherwise specified or there is a contradiction, the terms or phrases used in this invention have the following meanings:

[0040] In the present invention, "first" and "second" are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features.

[0041] In the description of the present invention, “plurality” means at least two, for example, two, three, etc., unless otherwise clearly and specifically defined.

[0042] In the present invention, "one or several" refers to any one, any two or any two or more of the listed items. Among them, "several" refers to any two or any two or more.

[0043] In the present invention, the percentage concentration involved, unless otherwise specified, refers to the final concentration. The final concentration refers to the proportion of the added component in the system after the addition of the component.

[0044] The words "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that may provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.

[0045] When a numerical range is disclosed in the present invention, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise indicated, all ranges disclosed in the present invention should be understood to include any and all subranges included therein.

[0046] In the present invention, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0047] The terms "including" and "having" and any variations thereof in the embodiments of the present invention are intended to cover non-exclusive inclusions. For example, a process, method, system, product, or device that includes a series of steps or units is not limited to the listed steps or units, but may optionally include steps or units that are not listed, or may optionally include other steps or components that are inherent to these processes, methods, products, or devices.

[0048] Reference to "embodiments" in the present invention means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in the present invention may be combined with other embodiments.

[0049] The inventors found in the experiment that the increase in NCM energy density brings with it the risk of reduced safety and lifespan. The reason is that Ni in NCM will participate in the electrochemical reaction. In the NCM system, Ni is generally in a mixed valence state of +2 and +3. As the de-lithiation increases, Ni 2+ Gradually oxidized to Ni 3+ , then oxidized to Ni 4+ , and Ni 4+ It has strong reducing property and is easy to produce Ni 4+ Transformed into Ni 3+ , so the oxygen and Ni in the material lattice 3+ , the electrolyte in the system undergoes oxidation reactions to maintain the charge balance of the system, which ultimately leads to a decrease in the electrochemical stability, mechanical stability and thermal stability of the material, posing a great challenge to the material's overcharge performance meeting the standards.

[0050] In view of the above problems, a first aspect of the present invention provides a composite positive electrode active material capable of improving overcharge resistance.

[0051] Specifically, the composite positive electrode active material includes a positive electrode active material matrix, a porous metal oxide coating layer disposed on the surface of the positive electrode active material matrix, and a conductive polymer coating layer disposed on the surface of the porous metal oxide coating layer.

[0052] Wherein, the positive electrode active material matrix includes a transition metal oxide material, and the transition metal oxide material includes nickel. Specifically, the positive electrode active material matrix includes a nickel-cobalt-manganese ternary material. Further, in the nickel-cobalt-manganese ternary material, the molar ratio of nickel, cobalt and manganese elements is (1-9):(1-9):(1-9). Further, in the transition metal oxide material, the percentage of the molar number of nickel element to the total molar number of transition metal elements is ≥60%, and optionally, the percentage of the molar number of nickel element to the total molar number of transition metal elements is ≥80%. For example, the percentage of the molar number of nickel element to the total molar number of transition metal elements can be, but is not limited to, 60%, 65%, 70%, 75%, 80%, 85%, 90% or a range consisting of any two of these values.

[0053] In a specific example, in the transition metal oxide material, the molar ratio of nickel, cobalt and manganese elements is Ni:Co:Mn=8:1:1.

[0054] In some embodiments, the material of the porous metal oxide coating layer is selected from any one or more of aluminum oxide, magnesium oxide, zirconium oxide, zinc oxide, yttrium oxide, nickel oxide, copper oxide and titanium oxide.

[0055] In some embodiments, the mass ratio of the porous metal oxide coating layer to the positive electrode active material matrix is ​​1: (200-10000). Optionally, the mass ratio of the porous metal oxide coating layer to the positive electrode active material matrix may be, but is not limited to, 1: 200, 1: 300, 1: 400, 1: 500, 1: 600, 1: 700, 1: 800, 1: 900, 1: 1000, 1: 2000, 1: 5000, 1: 8000, 1: 10000 or a range consisting of any two of these values. Preferably, the mass ratio of the porous metal oxide coating layer to the positive electrode active material matrix is ​​1: (200-500).

[0056] Under ultra-high voltage conditions, the lattice stability of the positive electrode active material decreases, and Ni 4+ A reduction reaction occurs, causing the lattice to transform from a layered structure to an unstable rock salt, and the oxygen in the lattice participates in charge replenishment, releasing oxygen and oxygen vacancies, thereby causing failure behavior. The porous metal oxide coating has good thermal stability, which helps to stabilize the crystal structure and inhibit surface side reactions. In addition, the porous structure helps the transmission of lithium ions, and is also beneficial for storing oxygen free radicals generated by the positive electrode active material matrix during overcharging, thereby slowing down the failure of the positive electrode active material overcharging. However, although a simple porous metal oxide coating can improve the overcharge resistance, it has a significant decrease in electrical conductivity and cannot be used in practice. Therefore, in this embodiment, a conductive polymer coating is formed on the surface of the porous conductive polymer coating to make up for the problem that the conductive capacity of the porous metal oxide coating decreases and cannot be used in practice.

[0057] In some embodiments, the material of the conductive polymer coating layer is selected from any one or more of polyaniline, doped polyaniline, polypyrrole, doped polypyrrole, polythiophene, doped polythiophene, polyphenylene sulfide and doped polyphenylene sulfide. Preferably, the conductive polymer comprises polyaniline. Polyaniline has the advantages of easy availability of raw materials, simple synthesis, relatively high conductivity, and wide application. Therefore, in this embodiment, the material of the conductive polymer coating layer is preferably polyaniline.

[0058] In some embodiments, at least a portion of the conductive polymer coating layer is located within pores on the surface of the porous metal oxide coating layer.

[0059] In some embodiments, the mass ratio of the conductive polymer coating layer to the porous metal oxide coating layer is (1-100): 1. For example, the mass ratio of the conductive polymer coating layer to the porous metal oxide coating layer can be, but is not limited to, 1:1, 10:1, 20:1, 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, 90:1, 100:1, or a range consisting of any two of these values.

[0060] The above composite positive electrode active material has at least the following advantages:

[0061] (1) The composite positive electrode active material comprises a positive electrode active material matrix, a porous metal oxide coating layer formed on the surface of the positive electrode active material matrix, and a conductive polymer coating layer. The electrochemically inert porous metal oxide coating layer has good thermal stability, which helps to stabilize the crystal structure and inhibit surface side reactions. In addition, the porous structure helps the transmission of lithium ions and is also conducive to the storage of oxygen free radicals generated by the positive electrode active material matrix during overcharging, thereby slowing down the overcharging failure of the positive electrode active material. The conductive polymer coating layer can compensate for the electrochemical inertness of the metal oxide and improve the electronic conductivity of the positive electrode active material.

[0062] (2) The above-mentioned composite positive electrode active material is first coated with a porous metal oxide coating layer to obtain a polymer conductive coating layer with good shape controllability, good dispersibility, and high structural regularity. The lattice conductive network is more uniform, and the conductive network on the particle surface is more uniform. The metal oxide coating layer contains a porous structure that is beneficial for storing oxygen free radicals generated by the positive electrode during overcharge. At the same time, the porous structure can be used as a template for the deposition of the conductive polymer coating layer, so that the conductive polymer coating layer has good shape controllability, good dispersibility, and high structural regularity, which is beneficial to improving the uniformity of the network structure of the positive electrode active material.

[0063] A second aspect of the present invention provides a method for preparing a composite positive electrode active material, comprising the following steps S110 to S120:

[0064] Step S110: forming a porous metal oxide coating layer on the surface of the positive electrode active material matrix.

[0065] Specifically, step S110 includes steps S111 to S113:

[0066] Step S111: mixing the raw materials for preparing the positive electrode active material matrix in the form of a metal salt solution with an aqueous solution containing a complexing agent to prepare a metal complex solution.

[0067] In some embodiments, the metal salt is selected from any one or more of metal sulfates, metal acetates and metal nitrates.

[0068] In a specific example, the raw materials for preparing the positive electrode active material matrix include nickel salt, cobalt salt, manganese salt and lithium salt. Specifically, in the raw materials for preparing the positive electrode active material matrix, the molar ratio of nickel, cobalt and manganese elements is (1-9):(1-9):(1-9). Preferably, the molar ratio of nickel, cobalt and manganese elements is Ni:Co:Mn=8:1:1.

[0069] In some embodiments, the complexing agent is selected from any one or more of inorganic phosphates, alcohol amines, aminocarboxylic acids, hydroxycarboxylates, organic phosphonates and polyacrylic acids. Optionally, the complexing agent is selected from any one or more of aminocarboxylic acids and hydroxycarboxylates. Specifically, the complexing agent is selected from any one or more of ethylenediaminetetraacetic acid (EDTA) and citric acid.

[0070] Specifically, the raw materials for preparing the positive electrode active material matrix are added into the aqueous solution containing the complexing agent in the form of a metal salt solution, and the mixture is stirred and mixed sufficiently to form a metal complex solution.

[0071] Step S112: Drying the metal complex solution to transform the sol into a gel.

[0072] Step S113: mixing the gel with the porous metal oxide, drying, and calcining to form a porous metal oxide coating layer on the surface of the positive electrode active material matrix.

[0073] In some embodiments, the porous metal oxide is selected from any one or more of porous aluminum oxide, porous magnesium oxide, porous zirconium oxide, porous zinc oxide, porous yttrium oxide, porous nickel oxide, porous copper oxide and porous titanium oxide. Preferably, the porous metal oxide comprises porous aluminum oxide.

[0074] In some embodiments, the average pore size of the porous metal oxide coating layer is 10nm to 900nm. Alternatively, the average pore size of the porous metal oxide can be, but is not limited to, 10nm, 50nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 550nm, 600nm, 650nm, 700nm, 750nm, 800nm, 850nm, 900nm or a range consisting of any two of these values. Preferably, the average pore size of the porous metal oxide coating layer is 400nm to 500nm.

[0075] In some embodiments, the porosity of the porous metal oxide coating layer is 50% to 90%. For example, the porosity of the porous metal oxide coating layer can be, but is not limited to, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90% or a range consisting of any two of these values.

[0076] In some embodiments, the specific surface area of ​​the porous metal oxide coating layer is 0.5 m 2 / g~1.5m 2 For example, the specific surface area of ​​the porous metal oxide coating layer can be, but is not limited to, 0.5 m 2 / g, 0.6m 2 / g, 0.7m 2 / g, 0.8m 2 / g, 0.9m 2 / g, 1m 2 / g, 1.1m 2 / g, 1.2m 2 / g, 1.3m 2 / g, 1.4m 2 / g, 1.5m 2 / g or a range consisting of any two of these values.

[0077] The above method can achieve mixing of reactants at the molecular level in a short time, and the elements of the prepared material are evenly distributed. Porous alumina is directly added to the gel and stirred to increase the contact area and make the coating more uniform.

[0078] In some embodiments, in the calcining step, the temperature is 700°C to 900°C and the time is 9h to 15h. Alternatively, the calcining temperature may be, but is not limited to, 700°C, 720°C, 750°C, 780°C, 800°C, 820°C, 850°C, 880°C, 900°C or a range consisting of any two of these values. The sintering time may be, but is not limited to, 9h, 10h, 11h, 12h, 13h, 14h, 15h or a range consisting of any two of these values.

[0079] Furthermore, before calcination, the method further comprises a step of grinding the dried product.

[0080] In some embodiments, the amount of raw materials for preparing the porous metal oxide and the positive electrode active material matrix added during the preparation process can be calculated based on the mass ratio of the porous metal oxide coating layer to the positive electrode active material matrix in the final prepared composite positive electrode active material of 1:(200-10000).

[0081] It can be understood that the above only provides a method for forming a porous metal oxide coating layer on the surface of the positive electrode active material matrix, but is not limited thereto.

[0082] In some embodiments, a preparation step of porous metal oxide is also included. Specifically, the preparation step of porous metal oxide can be commonly used in the art, for example, porous aluminum oxide is prepared by secondary anodization, porous zirconium oxide or porous magnesium oxide is prepared by coprecipitation, hydrothermal method, sol-gel method, etc.

[0083] In some embodiments, the preparation steps of the porous metal oxide include:

[0084] Step A: The electropolished metal is subjected to anodizing treatment.

[0085] Specifically, the step of primary anodization includes: using the graphite rod as a cathode, the electrolytically polished aluminum foil as an anode, and the first acidic solution as an electrolyte to perform primary anodization.

[0086] The concentration of the first acidic solution is 0.1 mol / L to 2.5 mol / L, the oxidation voltage is set at 10 V to 200 V, the oxidation time is 4 h to 10 h, and the temperature of the primary anodization is 0° C. to 10° C.

[0087] Specifically, the first acid solution may be, but is not limited to, oxalic acid, phosphoric acid, sulfuric acid solution, etc. During the primary anodization process, the electrolyte is placed in an ice water bath at a temperature of 0°C to 10°C.

[0088] Step B: Immerse the metal after the primary anodizing treatment in a mixture of phosphoric acid and chromic acid for reaction.

[0089] Specifically, the reaction temperature is 40°C to 80°C, and the reaction time is 5h to 8h. After the reaction is completed, a washing step is also included. Specifically, washing is performed with deionized water.

[0090] Specifically, in the mixed solution of phosphoric acid and chromic acid, the volume ratio of phosphoric acid to chromic acid may be, but is not limited to, 1:1.

[0091] The mixed solution treatment of phosphoric acid and chromic acid can dissolve the primary anodized film with poor order, leaving an ordered periodic pit interface on the metal substrate surface, so that an ordered porous oxide can be obtained when the porous metal oxide is prepared by the secondary anodizing method.

[0092] Step C: The metal immersed in the mixture of phosphoric acid and chromic acid is subjected to secondary anodizing treatment.

[0093] Specifically, the step of secondary anodization includes: using aluminum foil soaked in a mixture of phosphoric acid and chromic acid as an anode, graphite as a cathode, and a second acidic solution as an electrolyte to perform secondary anodization.

[0094] The concentration of the second acidic solution is 0.1 mol / L to 2.5 mol / L, the oxidation voltage is set at 10 V to 200 V, the oxidation time is 4 h to 10 h, and the temperature of the secondary anodization is 0° C. to 10° C.

[0095] Optionally, the second acidic solution may be, but is not limited to, oxalic acid, phosphoric acid, sulfuric acid solution, etc. It is understood that the second acidic solution may be the same as or different from the first acidic solution. During the secondary anodization process, the electrolyte is placed in an ice water bath at a temperature of 0°C to 10°C.

[0096] Step D: Stripping the porous metal oxide on the metal surface after the secondary anodizing treatment.

[0097] Specifically, the metal after the secondary anodization treatment is placed in a mixture of perchloric acid and ethanol, and the porous metal oxide is peeled off by a pulse method.

[0098] In a specific example, in the mixture of perchloric acid and ethanol, the perchloric acid and ethanol are in an equal volume ratio. The ethanol is preferably anhydrous ethanol.

[0099] Step E: Expand the pores of the porous metal oxide and sinter it to prepare the porous metal oxide.

[0100] Specifically, the pore expansion step includes: expanding the porous metal oxide in a phosphoric acid solution at a temperature of 20° C. to 40° C. for 10 min to 30 min.

[0101] Through the above steps, an orderly and regular porous metal oxide can be obtained.

[0102] Step S120: forming a conductive polymer coating layer on the surface of the porous metal oxide coating layer to obtain a composite positive electrode active material.

[0103] Wherein, the material of the conductive polymer coating layer is selected from any one or more of polyaniline, doped polyaniline, polypyrrole, doped polypyrrole, polythiophene, doped polythiophene, polyphenylene sulfide and doped polyphenylene sulfide. Preferably, the conductive polymer includes polyaniline. Polyaniline has the advantages of easy availability of raw materials, simple synthesis, relatively high conductivity, and wide application. Therefore, in this embodiment, the conductive polymer is preferably polyaniline.

[0104] In some embodiments, step S120 includes: mixing and stirring an acidic solution containing monomers for forming a conductive polymer with a positive electrode active material matrix coated with a porous metal oxide coating layer, and under the action of an initiator, allowing the monomers for forming a conductive polymer to be in situ polymerized using the pores in the porous metal oxide coating layer as a template to form a conductive polymer coating layer on the surface of the porous metal oxide coating layer.

[0105] Specifically, the monomer for forming the conductive polymer and the third acidic solution are mixed and stirred to obtain an acidic solution containing the monomer for forming the conductive polymer.

[0106] The monomers used to form the conductive polymer are selected from any one or more of aniline, pyrrole, thiophene and phenylene sulfide.

[0107] The concentration of the third acidic solution is 0.1 mol / L to 1 mol / L. Optionally, the concentration of the third acidic solution may be, but is not limited to, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L or a range consisting of any two of these values.

[0108] The third acidic solution includes any one of hydrochloric acid and phytic acid.

[0109] In some embodiments, during the process of mixing and stirring the monomer for forming the conductive polymer with the third acidic solution, the stirring time is greater than 30 min.

[0110] In some of the embodiments, the acidic solution containing the monomer for forming the conductive polymer and the positive electrode active material matrix coated with the porous metal oxide coating layer are mixed and stirred for 6 hours to 8 hours.

[0111] In some of the embodiments, the amount of the monomer added to form the conductive polymer is calculated based on a mass ratio of the conductive polymer coating layer to the porous metal oxide coating layer of (1-100):1.

[0112] In some embodiments, the initiator is added in the form of an acidic solution containing the initiator. Specifically, the initiator and the fourth acidic solution are mixed and stirred for 1 hour to 3 hours to obtain an acidic solution containing the initiator.

[0113] Specifically, the initiator may be, but is not limited to, ammonium persulfate. The fourth acidic solution includes any one of phytic acid and hydrochloric acid. The concentration of the fourth acidic solution is 0.1 mol / L to 1 mol / L. It is understood that the fourth acidic solution may be the same as or different from the third acidic solution, and preferably, the fourth acidic solution is the same as the third acidic solution.

[0114] In some embodiments, in the step of in-situ polymerization of the monomer for forming the conductive polymer using the pores in the porous metal oxide coating layer as a template, the mixture is stirred at 0°C to 10°C for 7h to 10h and then allowed to stand for 24h to 72h. Optionally, the temperature of the in-situ polymerization may be, but is not limited to, 0°C, 1°C, 2°C, 3°C, 4°C, 5°C, 6°C, 7°C, 8°C, 9°C, 10°C or a range consisting of any two of these values.

[0115] Furthermore, step S120 also includes: after the in-situ polymerization reaction is completed, filtering, washing and drying steps.

[0116] In the washing step, ultrasonic washing is performed twice with deionized water, ethanol, acetone, and deionized water in sequence.

[0117] In the drying step, the temperature is 60°C to 90°C and the time is 12h to 24h. Optionally, the drying temperature can be, but is not limited to, 60°C, 62°C, 65°C, 68°C, 70°C, 72°C, 75°C, 78°C, 80°C, 82°C, 85°C, 88°C, 90°C or a range consisting of any two of these values.

[0118] Since conductive polymers are difficult to dissolve and disperse, they have poor processability in the actual production process and are easy to agglomerate. In this embodiment, the conductive polymer coating layer is synthesized by a template method. Template synthesis refers to selecting an inorganic substance or a polymer with a certain pore structure as a template, and polymerizing the conductive polymer into the template pores through a polymerization reaction before forming a coating layer. The conductive polymer obtained by the template method has good shape controllability, good dispersibility, and high structural regularity. Therefore, in this embodiment, the porous metal oxide coating layer coated on the surface of the positive electrode active material becomes a good template for the synthesis of the conductive polymer, and the obtained conductive polymer is evenly dispersed and has a higher structural regularity, which solves the problem of difficult processing of the conductive polymer.

[0119] The above-mentioned method for preparing the composite positive electrode active material has at least the following advantages:

[0120] (1) The preparation method of the above-mentioned composite positive electrode active material adopts a double-layer step-by-step coating method. A layer of electrochemically inert porous metal oxide coating layer is first coated on the surface of the positive electrode active material matrix, which helps to stabilize the crystal structure and inhibit surface side reactions. At the same time, the porous material helps the transmission of lithium ions. Subsequently, a layer of conductive polymer is coated on the surface of the coated porous metal oxide coating layer to compensate for the electrochemical inertness of the metal oxide and improve the electronic conductivity of the positive electrode active material.

[0121] (2) The multilayer coating method of the above-mentioned composite positive electrode active material takes into account the advantages and disadvantages of porous metal oxides and conductive polymers. The porous metal oxides have good thermal stability, which helps to prevent the deformation of the crystal structure, but their electrochemical inertness reduces the electronic conductivity of the particles themselves; while the electrochemically active conductive polymers make up for the electrochemical inertness of the porous metal oxides and improve the electronic conductivity of the particles.

[0122] (3) The conductive polymer is prepared by the template in situ polymerization method. The porous metal oxide surface is used as a template and the conductive polymer is deposited along the pore wall. This is conducive to obtaining a conductive polymer coating with good shape controllability, good dispersion, and high structural regularity, thereby improving the conductive uniformity of the particle surface.

[0123] A third aspect of the present invention provides a positive electrode plate, comprising: a positive electrode current collector and an active material layer disposed on the positive electrode current collector, wherein the active material layer comprises the above-mentioned composite positive electrode active material.

[0124] It is understood that the positive electrode current collector is not particularly limited and may be any commonly used material in the art, such as aluminum foil.

[0125] It is understood that the active material layer may also include a conductive agent, a binder, etc. commonly used in the art.

[0126] A fourth aspect of the present invention provides a secondary battery comprising the above-mentioned positive electrode plate.

[0127] In some embodiments, in the secondary battery, the active material of the negative electrode is selected from one or more of artificial graphite, natural graphite, soft carbon, hard carbon, silicon carbon, silicon oxide, alloy, lithium titanate and metallic lithium.

[0128] It is understood that in a secondary battery, the negative electrode also includes a negative electrode current collector, and the active material of the negative electrode is formed on at least one surface of the negative electrode current collector. The negative electrode current collector is not particularly limited and can be commonly used in the art, such as but not limited to copper foil.

[0129] In some embodiments, the electrolyte solvent of the secondary battery is selected from any one or more of ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC) and methyl propyl carbonate (MPC).

[0130] In some embodiments, the separator of the secondary battery is not particularly limited and may be a separator commonly used in the art, such as, but not limited to, a porous polypropylene film.

[0131] In order to make the purpose and advantages of the present invention clearer, the composite positive electrode active material of the present invention and its effects are further described in detail in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and shall not be used to limit the present invention. The following embodiments do not include other components except inevitable impurities unless otherwise specified. The drugs and instruments used in the embodiments are conventionally selected in the art unless otherwise specified. The experimental methods for which specific conditions are not specified in the embodiments are implemented according to conventional conditions, such as the conditions described in the literature and books or the methods recommended by the manufacturer.

[0132] Example 1

[0133] This embodiment provides a composite positive electrode active material, and the preparation process is as follows:

[0134] 1. Preparation of porous alumina:

[0135] The aluminum foil after electrolytic polishing is first subjected to an anodic oxidation treatment, specifically including: using a graphite rod as a cathode and the aluminum foil after electrolytic polishing as an anode to be placed in an electrolytic device containing an oxalic acid solution, the concentration of the oxalic acid solution is 0.4 mol / L, the oxidation voltage is set to 40V, the oxidation time is 10h, and the temperature is placed in an ice water bath at 5°C. The aluminum foil after the primary anodization is immersed in a mixture of equal volumes of phosphoric acid and chromic acid, placed in a high temperature box set at 50°C for reaction, after reacting for 6 hours, rinsed with deionized water, and then subjected to secondary anodization, specifically including: using the aluminum foil soaked in phosphoric acid and chromic acid as an anode, graphite as a cathode, and conducting secondary anodization in an oxalic acid solution, the concentration of the oxalic acid solution is 0.4 mol / L, the oxidation voltage is set to 40V, the oxidation time is 10h, and the temperature is placed in an ice water bath at 5°C. The obtained secondary anodized aluminum foil is placed in a mixture of equal volumes of perchloric acid and anhydrous ethanol, and the porous oxide film is stripped by pulse. The porous oxide film was placed in a phosphoric acid solution with a temperature of 30° C. and a concentration of 1 mol / L for pore expansion for 25 minutes. After pore expansion, it was placed in a muffle furnace and heated to 300° C. for sintering for 5 hours to obtain the porous aluminum oxide of this embodiment.

[0136] 2. Preparation of Porous Alumina-Coated Cathode Active Materials

[0137] The corresponding metal acetates of nickel, cobalt and manganese are prepared according to the element molar ratio of 8:1:1, and then lithium acetate is added to provide a lithium source, and dissolved in deionized water to obtain a metal acetate aqueous solution.

[0138] Prepare ethylenediaminetetraacetic acid (EDTA) solution. During the preparation process, add an appropriate amount of ammonia water to ensure that EDTA is completely dissolved. Add the metal acetate aqueous solution to the ethylenediaminetetraacetic acid solution, stir and mix thoroughly at 80°C for 1h to form a metal complex solution. Evaporate the metal complex solution at 80°C to transform it from a sol to a gel. Add the above-mentioned porous alumina to the gel and mix, then place it in a drying oven at 100°C to dry it to obtain a dry gel. After the dry gel is fully ground, it is transferred to a tubular furnace, and the sintering temperature is set to 800°C and the sintering time is 10h to obtain a porous alumina-coated positive electrode active material, wherein the mass ratio of the porous alumina coating layer to the nickel-cobalt-manganese ternary material is 1:5000, and the average pore size of the porous alumina coating layer is 465nm.

[0139] 3. Preparation of composite positive electrode active materials:

[0140] Aniline was added to a 0.1 mol / L hydrochloric acid solution and stirred for 1 hour to form an aniline solution. The porous alumina-coated positive electrode active material obtained above was added to the aniline solution and stirred for 7 hours. Ammonium persulfate was mixed with a 0.1 mol / L hydrochloric acid solution and stirred for 2 hours to obtain an initiator solution. The initiator solution was slowly added dropwise to the aniline solution containing the porous alumina-coated positive electrode active material, stirred for 7 hours at a temperature of 2°C, and then allowed to stand for 24 hours, then filtered, and ultrasonically washed twice with deionized water, ethanol, acetone, and deionized water in sequence, and dried in an oven at 80°C for 12 hours to a dry state to obtain the composite positive electrode active material of this embodiment, wherein the mass ratio of the porous alumina coating layer to the polyaniline coating layer is 2:90.

[0141] Example 2

[0142] This embodiment provides a composite positive electrode active material, and the preparation process is as follows:

[0143] 1. Preparation of porous alumina:

[0144] The aluminum foil after electrolytic polishing is first subjected to an anodic oxidation treatment, specifically including: using a graphite rod as a cathode and the aluminum foil after electrolytic polishing as an anode to be placed in an electrolytic device containing an oxalic acid solution, placed in an ice water bath at a temperature of 5°C, the concentration of the oxalic acid solution is 0.4 mol / L, the oxidation voltage is set to 40V, and the oxidation time is 10h. The aluminum foil after the primary anodization is immersed in a mixture of equal volumes of phosphoric acid and chromic acid, placed in a high temperature box set at 50°C for reaction, after reacting for 6 hours, rinsed with deionized water, and then subjected to secondary anodization, specifically including: using the aluminum foil soaked in phosphoric acid and chromic acid as an anode, graphite as a cathode, and conducting secondary anodization in an oxalic acid solution, placed in an ice water bath at a temperature of 5°C, the concentration of the oxalic acid solution is 0.4 mol / L, the oxidation voltage is set to 40V, and the oxidation time is 10h. The obtained secondary anodized aluminum foil is placed in a mixture of equal volumes of perchloric acid and anhydrous ethanol, and the porous membrane is peeled off by pulse. The porous oxide film was placed in a phosphoric acid solution with a temperature of 30° C. and a concentration of 1 mol / L for 25 minutes for pore expansion. After pore expansion, the film was placed in a muffle furnace for heating and sintering at 300° C. for 5 hours to obtain the porous aluminum oxide of this embodiment.

[0145] 2. Preparation of Porous Alumina-Coated Positive Electrode Active Materials:

[0146] Prepare the corresponding metal acetates of nickel, cobalt and manganese according to the element molar ratio of 8:1:1, then add lithium acetate to provide a lithium source, dissolve in deionized water, and obtain a metal acetate aqueous solution. Prepare a citric acid aqueous solution. Add the metal acetate aqueous solution to the citric acid aqueous solution, stir and mix thoroughly for 1h to form a metal complex, and adjust the solution pH to 7-8 by adding diluted ammonia water. Evaporate the metal complex solution at 80°C to convert the sol into a gel, and obtain a precursor gel. Add the above-mentioned porous alumina to the precursor gel and mix, and then place it in a drying oven at 40°C to dry to obtain a dry gel. After the dry gel is fully ground, it is transferred to a tubular furnace, and the sintering temperature is set to 900°C and the sintering time is 9h to obtain a porous alumina-coated positive electrode active material, wherein the mass ratio of the porous alumina coating layer to the nickel-cobalt-manganese ternary material is 1:5000, and the average pore size of the porous alumina coating layer is 477nm.

[0147] 3. Preparation of composite positive electrode active materials:

[0148] Aniline was added to a 0.3 mol / L phytic acid solution and stirred for 1 hour to form an aniline solution. The porous alumina-coated positive electrode active material obtained above was added to the aniline solution and stirred for 8 hours. Ammonium persulfate was mixed with a 0.3 mol / L phytic acid solution and stirred for 2 hours to obtain an initiator solution. The initiator solution was slowly added dropwise to the aniline solution, stirred for 8 hours at a temperature of 5°C, and then allowed to stand for 36 hours, then filtered, ultrasonically washed twice with deionized water, ethanol, acetone, and deionized water, respectively, and dried in an oven at 80°C for 12 hours to a dry state to obtain the composite positive electrode active material of this embodiment. Among them, the mass ratio of the porous alumina coating layer to the polyaniline coating layer is 2:90.

[0149] Example 3

[0150] This embodiment provides a composite positive electrode active material, and the preparation process is similar to that of Embodiment 1, except that the mass ratio of the porous alumina coating layer to the nickel-cobalt-manganese ternary material is 1:200.

[0151] Example 4

[0152] This embodiment provides a composite positive electrode active material, and the preparation process is similar to that of Embodiment 1, except that the mass ratio of the porous alumina coating layer to the nickel-cobalt-manganese ternary material is 1:10000.

[0153] Example 5

[0154] This embodiment provides a composite positive electrode active material, and the preparation process is similar to that of Embodiment 1, except that polypyrrole is used to replace polyaniline.

[0155] Comparative Example 1

[0156] Comparative Example 1 provides a composite positive electrode active material, and the preparation process is similar to that of Example 1, except that it does not contain a conductive polymer coating layer, that is, it only includes step 1 of Example 1, preparation of porous alumina, and step 2 of Example 1, preparation of a porous alumina-coated positive electrode active material. Others are the same as Example 1.

[0157] Comparative Example 2

[0158] Comparative Example 2 provides a composite positive electrode active material, and the preparation process is as follows:

[0159] Prepare the corresponding metal acetates of nickel, cobalt and manganese according to the element molar ratio of 8:1:1, then add lithium acetate to provide a lithium source, dissolve in deionized water to obtain a metal acetate aqueous solution. Prepare ethylenediaminetetraacetic acid (EDTA) solution, add an appropriate amount of ammonia water to ensure that EDTA is completely dissolved. Add the metal acetate aqueous solution to the ethylenediaminetetraacetic acid (EDTA) solution, stir and mix thoroughly at 80°C for 1h to form a metal complex solution. Set the metal complex solution to 80°C to evaporate and transform it from sol to gel. Place the gel in a drying oven and dry it at 100°C to obtain a dry gel. After the dry gel is fully ground, transfer it to a tubular furnace, set the sintering temperature to 800°C, and the sintering time to 10h to obtain a nickel-cobalt-manganese ternary material.

[0160] Aniline was added to a 0.3 mol / L phytic acid solution and stirred for 1 hour to form an aniline solution. The nickel-cobalt-manganese ternary material obtained above was added to the aniline solution and stirred for 8 hours. Ammonium persulfate was mixed with a 0.3 mol / L phytic acid solution and stirred for 2 hours to obtain an initiator solution. The initiator solution was slowly added dropwise to the aniline solution, stirred for 8 hours at a temperature of 5°C, and then allowed to stand for 36 hours, then filtered, ultrasonically washed twice with deionized water, ethanol, acetone, and deionized water, respectively, and dried in an oven at 80°C for 12 hours to a dry state to obtain a polyaniline-coated positive electrode active material, i.e., the composite positive electrode active material of Comparative Example 2. Among them, the mass ratio of the polyaniline coating layer to the nickel-cobalt-manganese ternary positive electrode active material is 1:111.

[0161] Comparative Example 3

[0162] Comparative Example 3 provides a positive electrode active material, and the preparation process is as follows:

[0163] Prepare the corresponding metal acetates of nickel, cobalt and manganese according to the element molar ratio of 8:1:1, then add lithium acetate to provide a lithium source, dissolve in deionized water to obtain a metal acetate aqueous solution. Prepare ethylenediaminetetraacetic acid (EDTA) solution, add an appropriate amount of ammonia water to ensure that EDTA is completely dissolved. Add the metal acetate aqueous solution to the ethylenediaminetetraacetic acid (EDTA) solution, stir and mix thoroughly at 80°C for 1h to form a metal complex solution. Set the metal complex solution to 80°C to evaporate and transform it from sol to gel. Place the gel in a drying oven and dry it at 100°C to obtain a dry gel. After the dry gel is fully ground, transfer it to a tubular furnace, set the sintering temperature to 800°C, and the sintering time to 10h to obtain the positive electrode active material.

[0164] The positive electrode active material obtained above was prepared into a battery for testing, wherein the positive electrode active material used the positive electrode active material obtained in the above embodiment or comparative example, the negative electrode active material used artificial graphite, and the porous polypropylene film was used as a separator. The electrolyte solvent used a mixed solution of ethylene carbonate (EC), dimethyl carbonate (DMC), and diethyl carbonate (DEC).

[0165] The battery prepared as above was tested and compared with overcharge to confirm the effectiveness of the coating and DCR. The test results are shown in Table 1 below.

[0166] Overcharge test method:

[0167] The charging systems of 1C CC charging to 135% SOC and 0.1C CC charging to 165% SOC are respectively adopted. After completing the test steps, the battery is observed for 1 hour at the test environment temperature. If the test result is no fire or explosion, the test is judged to be passed.

[0168] DCR test method:

[0169] Discharge to 50% SOC at 1 / 3C, discharge at 2C for 10s, and let stand for 60min, thus calculating the 50% SOC discharge DCR.

[0170] Average pore size test method:

[0171] Before testing, the sample was placed in a vacuum drying oven at 60-80°C for 72 hours. After the sample was weighed, it was placed in a dilatometer and sealed. Low-pressure analysis was performed first, and then the dilatometer was removed from the low-pressure chamber and weighed again before high-pressure analysis. A curve of the relationship between pressure and injected mercury volume was obtained. By analyzing this curve, a series of average pore size parameters that characterize the sample can be obtained.

[0172] Table 1 Performance test of batteries prepared in various embodiments and comparative examples

[0173]

[0174] It can be seen from the above table that the composite positive electrode active material prepared in the embodiment significantly improves the overcharge resistance of the material and reduces the DCR.

[0175] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0176] The above-described embodiments only express several implementation methods of the present invention, which is convenient for understanding the technical solutions of the present invention in detail, but cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided by the present invention are all within the protection scope of the claims attached to the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the contents of the attached claims, and the description and drawings can be used to interpret the contents of the claims.

Claims

1. A composite positive electrode active material, characterized in that: include: A positive electrode active material matrix, a porous metal oxide coating layer arranged on the surface of the positive electrode active material matrix, and a conductive polymer coating layer arranged on the surface of the porous metal oxide coating layer.

2. The composite positive electrode active material according to claim 1, characterized in that: The composite positive electrode active material satisfies at least one of the following conditions: (1) The material of the porous metal oxide coating layer is selected from any one or more of aluminum oxide, magnesium oxide, zirconium oxide, zinc oxide, yttrium oxide, nickel oxide, copper oxide and titanium oxide; (2) The mass ratio of the porous metal oxide coating layer to the positive electrode active material matrix is ​​1:(200-10000); (3) The material of the conductive polymer coating layer is selected from any one or more of polyaniline, doped polyaniline, polypyrrole, doped polypyrrole, polythiophene, doped polythiophene, polyphenylene sulfide and doped polyphenylene sulfide; (4) at least a portion of the conductive polymer coating layer is located in the pores on the surface of the porous metal oxide coating layer; (5) The mass ratio of the conductive polymer coating layer to the porous metal oxide coating layer is (1-100):1; (6) The positive electrode active material matrix includes a transition metal oxide material, and the transition metal oxide material includes nickel element.

3. The composite positive electrode active material according to claim 2, characterized in that: In the transition metal oxide material, the percentage of the molar number of nickel element to the total molar number of transition metal elements is ≥60%.

4. A method for preparing a composite positive electrode active material, characterized in that: The steps include: (1) forming a porous metal oxide coating layer on the surface of the positive electrode active material matrix; (2) forming a conductive polymer coating layer on the surface of the porous metal oxide coating layer to obtain a composite positive electrode active material.

5. The method for preparing a composite positive electrode active material according to claim 4, characterized in that: The step of forming a porous metal oxide coating layer on the surface of the positive electrode active material matrix comprises: Mixing the raw material for preparing the positive electrode active material matrix in the form of a metal salt solution with an aqueous solution containing a complexing agent to prepare a metal complex solution; drying the metal complex solution to convert the sol into a gel; The gel is mixed with a porous metal oxide and calcined at 700° C. to 900° C. for 9 h to 15 h to form the porous metal oxide coating layer on the surface of the positive electrode active material matrix.

6. The method for preparing a composite positive electrode active material according to claim 5, characterized in that: The step of forming a porous metal oxide coating layer on the surface of the positive electrode active material matrix satisfies one or more of the following conditions: (1) The complexing agent is selected from any one or more of inorganic phosphates, alcohol amines, aminocarboxylic acids, hydroxycarboxylates, organic phosphonates and polyacrylic acids; (2) preparing the porous metal oxide by secondary anodizing treatment; (3) The average pore size of the porous metal oxide coating layer is 10 nm to 900 nm; (4) The porosity of the porous metal oxide coating layer is 50% to 90%; (5) The specific surface area of ​​the porous metal oxide coating layer is 0.5 m 2 / g~1.5m 2 / g.

7. The method for preparing a composite positive electrode active material according to claim 4, characterized in that: The step of forming a conductive polymer coating layer on the surface of the porous metal oxide coating layer comprises: An acidic solution containing monomers for forming the conductive polymer is mixed and stirred with a positive electrode active material matrix coated with a porous metal oxide coating layer. Under the action of an initiator, the monomers for forming the conductive polymer are in situ polymerized using the holes in the porous metal oxide coating layer as a template to form the conductive polymer coating layer on the surface of the porous metal oxide coating layer.

8. The method for preparing a composite positive electrode active material according to claim 7, characterized in that: The step of forming a conductive polymer coating layer on the surface of the porous metal oxide coating layer satisfies one or more of the following conditions: (1) in the step of allowing the monomer for forming the conductive polymer to be in-situ polymerized using the pores in the porous metal oxide coating layer as a template, first stirring at 0° C. to 10° C. for 7 h to 10 h, and then standing for 24 h to 72 h; (2) The monomer used to form the conductive polymer is selected from any one or more of aniline, pyrrole, thiophene and phenylene sulfide; (3) The acidic solution includes any one of hydrochloric acid and phytic acid.

9. A positive electrode sheet, characterized in that: include: A positive electrode current collector and an active material layer arranged on the positive electrode current collector, wherein the active material layer comprises the composite positive electrode active material according to any one of claims 1 to 3 or a composite positive electrode active material prepared by the method for preparing the composite positive electrode active material according to any one of claims 4 to 8.

10. A secondary battery, characterized in that: Comprising the positive electrode sheet as described in claim 9.

Citation Information

Cited By

  • Overcharge monitoring and automatic cutting-off system and method for lithium battery of communication equipment

    CN121216079A

  • An automatic cut-off system and method for overcharge monitoring of lithium batteries for communication equipment

    CN121216079B

  • Phosphate positive electrode material and preparation method thereof, positive plate and secondary battery

    CN121439768A

  • Positive electrode material, preparation method thereof and electrochemical device

    CN121460557A